The cost-effectiveness of education and support group interventions aimed at promoting breastfeeding. - Mavranezouli, Ifigeneia; Rajesh, Sharangini; Deshpande, Shalmali; Swanson, Vivien; Wright, Charlotte; Ross, Samantha; Sibson, Victoria L; McLean, Karen; Kambo, Anita; Fisher, Shereen (European Journal of Public Health, 2026)
Breastfeeding, especially exclusive, is associated with long-lasting health benefits to mothers and babies and healthcare cost-savings; however, breastfeeding rates are low in many high-income countries. Education and support interventions are effective in promoting breastfeeding but evidence on their cost-effectiveness is limited, uncertain, or negative. Our study objective was to assess the cost-effectiveness of group-based breastfeeding interventions from the National Health Service (NHS) and Personal Social Services (PSS) perspective in England. We used decision-analytic modelling to estimate incremental costs, clinical benefits (prevention of infections and death in babies, prevention of breast cancer in mothers) and quality-adjusted life-years (QALYs) of group breastfeeding interventions from the NHS/PSS perspective in England. A systematic review and meta-regression of randomized controlled trials was performed to estimate intervention effectiveness, while data on the benefits of breastfeeding were obtained from large published meta-analyses. Other model inputs were derived from published literature and national statistics. Compared with standard care alone, group breastfeeding interventions resulted in fewer infections and deaths in babies, fewer cases of breast cancer in mothers and higher QALYs (0.004 per mother-baby dyad), through increased rates of breastfeeding, and yielded cost-savings (£89 per mother-baby dyad) that outweighed intervention costs (£28 per mother-baby dyad). Group interventions that promote breastfeeding by providing education, advice and support to mothers are likely cost-effective in England. Further research should enhance the evidence base on the clinical and cost-effectiveness of breastfeeding interventions, considering their differential effects on different socioeconomic groups and a wider range of clinical benefits of breastfeeding.